Introduction to Microsystem Design - Schomburg, Werner Karl.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The book describes the design of micro systems systematically as well as the equations needed for an estimation of the basic elements. It can be used without knowing fabrication processes of micro systems and provides the basic equations needed to calculate the effects and forces which are important in micro systems. For quick reference equations are presented in tables which are found in an index at the end of this book.
Preface -- Notations and symbols -- Introduction -- Scaling Laws -- Elastic deformations -- Thin Films -- Conductor Paths -- Membranes -- Strain gauges on membranes -- Beams -- Vibrations -- Capillaries -- Capacitive forces -- Piezoelectric effect -- Thermal actuators -- Micro optics -- Diffusion -- Micro valves -- Micro pumps -- Micro dosing -- Analogies between physical domains -- Mechanical devices for electronics -- Pressure sensors -- Flow sensors -- Inertial sensors.
Keywords: Engineering; Systems engineering; Optical materials; Engineering; Nanotechnology and Microengineering; Optical and Electronic Materials; Applied and Technical Physics; Circuits and Systems